A DCOR-BASED NPD PROCESS REDESIGN APPROACH WITH GROUNDED THEORY EVALUATION - Ou-Yang, Chao; Yin, I-Hsiu; Juan, Yeh-Chun (The South African Journal of Industrial Engineering, 2019)
This research proposes a benchmarking-based process redesign approach for a new product development (NPD) process. The proposed method compares the semantic similarities of the design activities in the as-is NPD process with the activities in the design chain operations reference-model (DCOR). Then a design structure matrix (DSM) is employed to streamline the redesigned NPD process and form a to-be NPD process. Finally, grounded theory is used to evaluate the to-be NPD process according to five key performance indicators and to identify the pros and cons for the redesign changes. An unmanned aerial vehicle (UAV) NPD process is used for case study and the results show that the to-be UAV NPD process is more effective than the as-is UAV NPD process.